Assessment of drug-drug interactions among patients with psychiatric disorders: A clinical pharmacist-led study - Selas Sunny; Santosh Prabhu; Sharad Chand; Nandakumar UP; Chinju Susan Chacko; Juno J. Joel (Elsevier, 2022)
Background: Drug-drug interaction alters the efficacy of the drugs. Early identification can reduce unintended therapeutic outcomes. Objective: The main objective of the present study was to assess the drug-drug interactions among patients with psychiatric disorders. Methodology: A prospective observational study was conducted for a period of eight months. A total of 112 psychiatric inpatients were enrolled in the study. The patients were monitored regularly to identify the incidence of potential and actual drug-drug interactions. The identified interactions were analyzed for their severity by using various standard references which included published scientific articles, online databases (e.g., UpToDate) and standard textbooks. Results and Discussion: The mean age of the study population in years was found to be 37.93 ± 12.21 standard deviation. It was observed that the incidence of potential drug-drug interactions was 66.96%. A total of 201 potential drug-drug interactions were identified from 75 patients. Based on the severity assessment of the identified interactions, 52.73% were major, 37.31% were moderate, and 19.82% were minor. About 7.46% were contraindicated drug combinations. The data on the onset of interaction revealed that 34.82% were of delayed onset and 14.92% with rapid onset and 50.24% were not specified. The drug that was responsible for the majority of the interactions in the study was found to be olanzapine. Conclusion: The study revealed a high incidence of drug-drug interaction. Drug-drug interactions most frequently encountered among psychiatric patients were found to be major in terms of severity. The study concluded on the higher event of drug-drug interactions among the patients prescribed with olanzapine.